Government Expenditure, Human Development Index and Regional Inequality in Indonesia - Alfons, Marlyn E; ., Nursini; Rahman R, Abd (Journal of Ecohumanism, 2024)
This study was conducted with the aim of measuring and analyzing the effect of regional government spending on regional inequality through the Human Development Index in Indonesia. This analysis was conducted using the Williamson index as an indicator of regional inequality. This study uses variables of human development spending, infrastructure spending, economic spending, human development index and regional inequality. The research method used is the statistical panel data approach of 34 provinces in Indonesia in 2017-2023 with the Multiple Regression Equation model with AMOS program path analysis. The test results in this study state that directly the variables of human development spending, infrastructure spending, economic spending, and the human development index have a significant effect on regional inequality in Indonesia. Indirectly, the variables of human development spending and economic spending have a significant effect on regional inequality in Indonesia through the human development index, while the variable of infrastructure spending does not affect regional inequality through the human development index.